2010
DOI: 10.1136/tc.2009.031047
|View full text |Cite
|
Sign up to set email alerts
|

Using a cessation-related outcome index to assess California's cessation progress at the population level

Abstract: BackgroundThe California Tobacco Control Program (CTCP) has employed strategies to change social norms around smoking in order to decrease the prevalence of smoking and tobacco-related diseases. Research is scarce on CTCP's impact on overall smoking cessation in California.MethodsTobacco Use Supplement to the Current Population Survey (TUS-CPS) data from 1992–1993 to 2006–2007 was used to create a cessation-related outcome index (CROI), which was a summarised z score of the following determinants: plan to quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We reluctantly excluded literature on California's landmark programme, the first to feature a strong TID component, because published reports merged TID and other social norm change components into a single construct; these could not be separately analysed. However, California programme evaluations suggest that TID has been an important element in increasing quitting, reducing smoking prevalence and increasing support for tobacco control 2 3 73–76. Heterogeneity in TID interventions and outcome measures did not allow quantitative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We reluctantly excluded literature on California's landmark programme, the first to feature a strong TID component, because published reports merged TID and other social norm change components into a single construct; these could not be separately analysed. However, California programme evaluations suggest that TID has been an important element in increasing quitting, reducing smoking prevalence and increasing support for tobacco control 2 3 73–76. Heterogeneity in TID interventions and outcome measures did not allow quantitative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has found that although changing social norms at a community level is diffi cult, once accomplished these changes are particularly sustainable (Latkin et al, 2003). For example, anti-smoking campaigns and legislation in the United States have greatly reduced smoking rates on a broad level (Middlestadt et al, 2011;Tang et al, 2010;Zhu et al, 2007). In addition, interventions to reduce drinking and/or alter patterns of substance use have directly targeted changing social norms with some success (LaBrie et al, 2009;Latkin et al, 2009;Moreira et al, 2009;Neighbors et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…California has been a natural laboratory and an exemplar for antismoking policies in the United States and around the world. [1][2][3] Although much progress has been made in the United States and California in reducing tobacco prevalence, exposure to secondhand smoke (SHS) still impacts more than 126 million nonsmoking Americans. 4 Disproportionate exposure to SHS among minority groups, including Hispanic(s)/Latino(s) (H/L), could exacerbate tobacco-related health disparities.…”
Section: Purposementioning
confidence: 99%